Overview of mechanism and consequences of endothelial leakiness caused by metal and polymeric nanoparticles - Lasak, Magdalena; Ciepluch, Karol (Beilstein Journal of Nanotechnology, 2023)
Nanoparticles (NPs) exhibit unique physicochemical properties that enable them to overcome biological barriers and to be considered one of the best materials with anticancer properties. Most of the administered NPs that end up in the bloodstream interact with the endothelial layer. The interaction of the NPs with the endothelium widens the existing gaps or induces new ones in the monolayer of vascular endothelial cells, thus increasing the access to the target sites in the organism. This type of interaction can lead to NP-modulated endothelial leakiness (NanoEL). The most important factors determining NanoEL are the physicochemical properties of the NPs. NP-modulated endothelial leakiness can lead to the discovery of new therapeutic targets and strategies to improve drug delivery through controlling and regulating NanoEL. Nevertheless, the NanoEL mechanism also carries some limitations that result from an incomplete understanding of NP metabolism and toxicity, and the possibility of their participation in the unintended bidirectional vascular permeability, which may contribute to the formation of cancer metastases. In this review we are focusing on the effect of metal and polymeric NPs on mechanism and degree of induction of NanoEL, as well as on the benefits and risks of using NPs that induce endothelial leakiness.
Keywords: endothelial leakiness; metal nanoparticles; NanoEL; nanotoxicity; vascular permeability